Extended cleavage specificities of human granzymes A and K, two closely related enzymes with conserved but still poorly defined functions in T and NK cell-mediated immunity - Aybay, Erdem; Ryu, Jinhye; Fu, Zhirong; Akula, Srinivas; Enriquez, Erika Mendez; Hallgren, Jenny; Wernersson, Sara; Olsson, Anna-Karin; Hellman, Lars (Frontiers in Immunology, 2023)
Granzymes A and K are two highly homologous serine proteases expressed by mammalian cytotoxic T cells (CTL) and natural killer cells (NK). Granzyme A is the most abundant of the different granzymes (gzms) expressed by these two cell types.Gzms A and K are found in all jawed vertebrates and are the most well conserved of all hematopoietic serine proteases. Their potential functions have been studied extensively for many years, however, without clear conclusions. Gzm A was for many years thought to serve as a key component in the defense against viral infection by the induction of apoptosis in virus-infected cells, similar to gzm B. However, later studies have questioned this role and instead indicated that gzm A may act as a potent inducer of inflammatory cytokines and chemokines. Gzms A and K form clearly separate branches in a phylogenetic tree indicating separate functions. Transcriptional analyses presented here demonstrate the presence of gzm A and K transcripts in both CD4 + and CD8 + T cells. To enable screening for their primary biological targets we have made a detailed analysis of their extended cleavage specificities. Phage display analysis of the cleavage specificity of the recombinant enzymes showed that both gzms A and K are strict tryptases with high selectivity for Arg over Lys in the P1 position. The major differences in the specificities of these two enzymes are located N-terminally of the cleavage site, where gzm A prefers small amino acids such as Gly in the P3 position and shows a relatively relaxed selectivity in the P2 position. In contrast, gzm K prefers large amino acids such as Phe, Tyr, and Trp in both the P2 and P3 positions and does not tolerate negatively charged residues in the P2 position. This major distinction in extended specificities is likely reflected also in preferred in vivo targets of these two enzymes. This information can now be utilized for high-precision screening of primary targets for gzms A and K in search of their highly conserved but still poorly defined functions in vertebrate immunity.